Hunters, Crown, Nobles, and Conservation Elites: Class Antagonism over the Ownership of Common Fauna. Issue 2 (23rd June 2017) - von Essen, Erica; Allen, Michael; Hansen, Hans Peter
Abstract: Because of their status of res nullius —owned by no one—property theory is underdeveloped in regard to wildlife. In this article, wildlife is seen to be sometimes subject to a shadow ownership by class interests in society. Hunters accuse protected wolves of being the "pets" or "property" of an urban-based conservationist middle class. This phenomenon fragments the common fauna and undermines responsibility taking and policy compliance for wildlife that is seen as being owned by an oppositional social class. Using an empirical case study of Swedish hunters, we show how responsibility for wildlife has become entangled with property rights. A historical materialist analysis reveals that hunters once experienced ownership of wildlife by the nobility as co-opting state coercive power. Today, however, aristocracy is replaced by a new elite class of conservationists. Noting the hunters' tendency to evoke quasi-aristocratic virtues of ownership, we advance recommendations for an alternative approach. We appeal to deliberative democracy to promote the "communing" of wildlife across classes in fora that withstand co-optation by class interests.